2021
DOI: 10.1055/s-0040-1719221
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Calcifying Pseudoneoplasms of the Neural Axis in Lumbar Spine

Abstract: Calcified pseudoneoplasm of the neural axis (CAPNON) is a very rare, non-neoplastic, calcified pathological entity occurring anywhere in the central nervous system (CNS). Overall, less than 100 cases were reported, of which less than 50% were from the spine. We present a case of a 53-year-old lady with a history of L4–L5 radiculopathy, known case of rheumatoid arthritis, and with no previous history of trauma, tumor or infection. MRI showed calcified intradural mass, extending into the right lateral recess, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…It is difficult to suspect and diagnose the disease with only conventional imaging workup such as MRI, computed tomography (CT) scans and X-rays. The tumor usually displays partial calcifications on CT scans and on the MRI it usually shows a well-defined hypointense lesion in T1 and T2 weighted images along with limited hyperintensity after contrast enhancement T1 weighted imaging 13,15,20) . Due to these non-specific characteristics of the tumor, it is crucial for physicians to rule out other more common possible disease entities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to suspect and diagnose the disease with only conventional imaging workup such as MRI, computed tomography (CT) scans and X-rays. The tumor usually displays partial calcifications on CT scans and on the MRI it usually shows a well-defined hypointense lesion in T1 and T2 weighted images along with limited hyperintensity after contrast enhancement T1 weighted imaging 13,15,20) . Due to these non-specific characteristics of the tumor, it is crucial for physicians to rule out other more common possible disease entities.…”
Section: Discussionmentioning
confidence: 99%
“…In the case presented in this study it showed similar results where it showed hyalinized leiomyoma (positive for smooth muscle markers, SMA, desmin, negative for the expression of factor XIII); Inflammatory myofibroblastic tumor (negative for SMA expression and only sporadically positive for Keratin and desmin expression, while always positive for the expression of factor XIIIa and ALK). 4) 1993 Lumbar None Improved Mayr et al 15) 2000 Cervical and thoracic None Improved Liccardo et al 12) 2003 Dorsal None Improved Aiken et al 1) 2009 Dorsal None Not described Mahapatra et al 16) 2010 Lumber None Improved Naidu et al 17) 2012 Lumbar None Improved Nathoo et al 18) 2012 Lumbar None Improved Stienen et al 19) 2013 Lumber None Improved Kocovski et al 11) 2015 Lumbar Not described Not described Lopes et al 13) 2016 Lumbar None Improved García Duque et al 5) 2016 Cervical, dorsal, and lumbar None Improved Gauden et al 6) 2019 Cervical None Improved Ho et al 8) 2020 Cervical, dorsal, and lumbar None Variable Ravi et al 20) 2022 Lumbar None Improved…”
Section: Discussionmentioning
confidence: 99%